(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In article the problem of definition of the Internet as the semantic space formed by the sites is considered. The thought that the site text represents new type of a discourse – the computer mediated discourse locates. In article classification of discourse types is presented and proved, strategy of the communication which is carried out on the site of the companies are allocated. The text of the site is considered as persuasive type of the discourse having intension of presentation of Bank in certain ways of speech influence. The sites of the bank companies with the purpose to track features of formation and functioning of presentation type of a site discourse and ways of its speech impact on target audience as the instrument of creation of positive image of Bank are analyzed. The technologies used by Bank for customer acquisition in certain ways of speech influence are analysed. The conclusion about features of functioning of a presentation discourse of the site is as a result made, ways of formation positively of image of the company through speech influence on the sites of different banks are compared.